Structural model of university social responsability (Sustainability in Debate, 2021)
The study aims to analyze the University Social Responsibility (USR) policy implemented at the Michoacan State University (Universidad Michoacana de San Nicolás de Hidalgo - UMSNH) from the perspective of the university community. For that purpose, a Structural Equations Model in its variant of Partial Least Squares (PLS) was used from a theoretical/empirical construct on the USR. Five variables integrated into 17 indicators were used, obtained by a representative sample. The results are presented in two sections; a) USR performance at the UMSNH and; b) the role of each variable in the PLS model. It is concluded that the performance was regular and the Internal Management (IM) had a key impact on the model operation. In the management practice, this might help identify areas to improve the performance of this policy by sector and variables.